2016
DOI: 10.1021/jacs.6b03785
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into C–H Oxidations by Ruthenium(III)-Pterin Complexes: Impact of Basicity of the Pterin Ligand and Electron Acceptability of the Metal Center on the Transition States

Abstract: A ruthenium(II) complex, [Ru(dmdmp)Cl(MeBPA)] (2) (Hdmdmp = N,N-dimethyl-6,7-dimethylpterin, MeBPA = N-methyl-N,N-bis(pyridylmethyl)amine), having a pterin derivative as a proton-accepting ligand, was synthesized and characterized. Complex 2 shows higher basicity than that of a previously reported Ru(II)-pterin complex, [Ru(dmdmp) (TPA)](+) (1) (TPA = tris(2-pyridylmethyl)amine). On the other hand, 1e(-)-oxidized species of 1 (1OX) exhibits higher electron-acceptability than that of 1e(-)-oxidized 2 (2OX). Bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 106 publications
(96 reference statements)
1
7
0
Order By: Relevance
“…Conversely, no apparent correlation exists with the p K a of organic substrates (Figure S4), ruling out a p K a driven mechanism. Instead, the linear correlation implicates a concerted H-atom abstraction pathway, and this observation is consistent with other metal complexes that react via a CPET mechanism. Additionally, large differences between the p K a values of 4 and C–H substrates (Δp K a > 30) and between the E ° values of 2 (Co III/IV couple) and C–H substrates (Δ E ° > 0.6 V) suggest that discrete proton or electron transfer is not thermodynamically accessible, disfavoring stepwise proton transfer-electron transfer (PTET) and electron transfer-proton transfer (ETPT) pathways. Taken together, these data strongly suggest that H-atom abstraction by 2 occurs by a CPET mechanism.…”
Section: Results and Discussionsupporting
confidence: 74%
“…Conversely, no apparent correlation exists with the p K a of organic substrates (Figure S4), ruling out a p K a driven mechanism. Instead, the linear correlation implicates a concerted H-atom abstraction pathway, and this observation is consistent with other metal complexes that react via a CPET mechanism. Additionally, large differences between the p K a values of 4 and C–H substrates (Δp K a > 30) and between the E ° values of 2 (Co III/IV couple) and C–H substrates (Δ E ° > 0.6 V) suggest that discrete proton or electron transfer is not thermodynamically accessible, disfavoring stepwise proton transfer-electron transfer (PTET) and electron transfer-proton transfer (ETPT) pathways. Taken together, these data strongly suggest that H-atom abstraction by 2 occurs by a CPET mechanism.…”
Section: Results and Discussionsupporting
confidence: 74%
“…The α values (0.91 for 1 and 0.62 for 2) suggest that the transition states of the HAT reactions by 1 and 2 should be rather late and product-like. 31,33 In order to clarify the comparative energy levels between 1 and 2 in the DHA oxidation, a plausible energy diagram is proposed as shown in Scheme 3. It is important to consider the energy level of Cr IV (OH) species as an initial product in the stepwise HAT reaction, which is also related to that of Cr III species at the final product state.…”
Section: ■ Results and Discussionmentioning
confidence: 51%
“…The slope of the plot was determined to be 0.91 for 1 and 0.62 for 2 based on the Evans–Polanyi equation (eqs , ): , where Δ H is related to the BDE values of C–H bonds of substrates and O–H bonds of Cr V (O)/Cr IV (OH) and α is a standard value for the thermochemistry of the overall HAT reactions. The α values (0.91 for 1 and 0.62 for 2 ) suggest that the transition states of the HAT reactions by 1 and 2 should be rather late and product-like. , …”
Section: Resultsmentioning
confidence: 99%
“…Among a series of M n + (O) complexes, high-valent Ru-oxo complexes have also been intensely investigated as active species in substrate oxidation reactions, including C–H oxidation. It has been revealed that C–H oxidation of cumene by Ru IV (O) complexes is initiated by hydrogen atom abstraction, followed by an oxygen-rebound process to afford cumyl alcohol in CH 3 CN. , In the course of HAT from the C–H bond to a Ru IV (O) complex, the CPET pathway has been accepted in light of arguments based on the Bell–Evans–Polanyi principle; , however, the influence of protons on the asynchronicity of CPET from a C–H bond to a Ru IV (O) complex has yet to be scrutinized.…”
Section: Introductionmentioning
confidence: 99%